Progress in geography key stage 3 - Gardner, David; Coles, Jo; Hopkins, Eleanor; Lyon, John; Owen, Catherine (Dynamic learning, 2018)
Motivate pupils to develop their geographical skills, knowledge and understanding as they become engaged and accomplished geographers, ready for the demands of GCSE. Specifically designed to provide a solid foundation for the 2016 GCSE specifications, this Student Book takes an enquiry-based approach to learning within each unit and lesson. - Easily and cost-effectively implement a new KS3 scheme of work: this coherent single-book course covers the latest National Curriculum content, providing 150 ready-made lessons that can be used flexibly for a two or three-year KS3 - Build and improve the geographical knowledge and skills that pupils need: every double-page spread represents a lesson, with rich geographical data and place contexts for pupils to interpret, analyse andevaluate - Lay firm foundations for GCSE: key vocabulary, command words and concepts are introduced gradually, preparing pupils for the content and question types they will encounter at GCSE, with a particular focus on analysis and evaluation questions - Effectively assess, measure and demonstrate progress: formative assessments throughout each lesson and summative end-of-unit reviews include questions that show whether pupils are 'working towards', 'meeting' or 'exceeding' expectations - Encourage pupils to check and drive their own progress: learning objectives and end-of-unit learning outcomes help pupils reflect on their learning and make connections between key concepts and skills throughout the course